FRAUD DETECTION ANALYSIS OF PRESENTATION OF FINANCIAL STATEMENTS OF PROPERTY AND REAL ESTATE COMPANIES ON THE INDONESIA STOCK EXCHANGE, 2018-2019 - Surbakti Karo karo; Jihen Ginting; Jumiadi AW; Yesica Sinulingga (CERED Indonesia Institute, 2021)
The aim of this research was to test the effects of fraud diamond on fraudulent financial statement. The samples of this research is property and real estate companies listed on Indonesia Stock Exchange (IDX) in 2017 to 2018 periods. The number of companies were 40 companies with 2 years observation. Based on purposive sampling method, sample total is 80. The data analysis methods used logistic regressions. Data were collected using a secondary data in the form of annual report that were downloaded from www.idx.co.id. The method of data analysis used in this study was logistic regression using SPSS 26.0 . The results of these research indicate thatfinancial stability, external pressure, financial target, nature of industry ratio, audit opinion and director change has no significant impact on fraudulent financial statement (Beneish M-Score) with 0.649, 0.142, 0.658, 0.750, 0.999 and 0.545 significant value.